CAREER INFORMATION PROCESSING MODEL UNTUK MEMBANTU KEPUTUSAN KARIR SISWA KELAS IX DI SMP NEGERI 11 PONTIANAK - Pasaribu, Ruth Regina Megaputri; Yuline; Yanti, Elli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low career decision-making ability of ninth-grade students at SMP Negeri 11 Pontianak, which is characterized by students' confusion in determining further education choices that suit their potential. Theoretically, this research is based on the Career Information Processing Model (CIP), which views career decision-making as a cognitive-based problem-solving process through self-understanding, knowledge of career options, and systematic decision-making skills. This research aims to test the effectiveness of the Career Information Processing Model in helping ninth-grade students' career decisions. The research method used is an experimental method with a quantitative approach using a Pre-Experimental design in the form of a One-Group Pretest–Posttest Design. The research sample was determined through a purposive sampling technique involving 67 students of grades IX D and IX E. Data were collected using a career decision questionnaire that had met the validity and reliability tests, then analyzed using the Paired Sample T-test. The results showed that the average score of students' career decisions before treatment was 82.39 and increased to 108.76 after being given information services based on the CIP Model. The statistical test results showed a significance value of p < 0.05, indicating a significant difference between before and after treatment. Thus, it can be concluded that the Career Information Processing Model is effective in helping improve the career decisions of ninth-grade students at SMP Negeri 11 Pontianak.